Development Tin-Chromium Pillared in Bentonite as Catalyst for Ethanol to Gasoline Conversion (Asian Journal of Applied Sciences, 2019)
Bentonite is a natural material that can used as a buffer catalysts and easy to modified. Tin and Chromium metals can used as catalyst material. Tin and Chromium metals supported into bentonite was successfully prepared by pillarization method, and was calling Bi-Oxides pillared clays. It has used to catalyst for ethanol to gasoline conversion. Basal spacing for bentonite and Sn-Cr/bentonite were 12,83Ǻ and 25,67Ǻ respectively. Specific surface area and pore volume of Sn-Cr/bentonite was investigated and appeared be bigger than bentonite. The results confirmed by BET analysis that were 30,35 m2/g become 168,86 m2/g and pore volume from 0,0065cm3/g become 0,03 cm3/g. The thermal stability was determined by Thermogravimetry Analysis from temperature 0ºC until 1000ºC and the functional group changes detected by Fourier Transform Infra Red. XRF and EDX detected the Sn-Cr metals in the bentonite. The results of the liquid catalyst test analyzed by GC-MS and showed the contents consisted of benzene, toluene, octane, and naphthalene, that were similar with commercial gasoline. So, the Sn and Cr were using as metal pillars for bentonite interlayer and successfully used this Bi-oxides pillared clays for ethanol to gasoline conversion. Keywords— Bi-Oxides, Pillared clays, Sn-Cr/Bentonite, Ethanol to Gasoline.